Meaning of Clothes and Equipment of Minangkabau Adat Rules in Nagari Labuh District Flat Soil - Muhammad Rahmatullah (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2020)
ABSTRACTMinangkabau is located in West Sumatra Province. In this area there are many cultural heritages, one of which is clothing. In daily life, the Minangkabau people have long recognized the difference between everyday clothes and clothes for traditional ceremonies and how they are placed, one of which is the traditional leader. In traditional ceremonies, traditional leaders usually wear traditional clothing from head to toe. The meaning of traditional ruler clothing and equipment has now undergone a shift so that the younger generation has not paid attention.The results obtained in this study are the meaning of traditional ruler clothing in Nagari Labuh or Luhak Tanah Datar, Saluak is a head covering which has two halves, meaning Koto Piliang harmony. and Body Harmony Caniago. The black shirt of the Gadang Langan is the clothing of the traditional leader which means courage, selflessness, a sign of greatness, and is free to make decisions according to customary law. Clothing is a cloth which means that you have to be generous in accepting nephews who violate the customary order. Sarawa Hitam Gadang Kaki has the meaning of being responsive and spontaneous in solving problems in the lives of children and nephews. Besides the meaning is courage, truth, and depth of knowledge. Cawek is a belt that means being able to overcome stubborn nephews in order to remain obedient. Sandals are leather sandals that show dignity and authority. Karih means the greatness of the customary leader to protect his nephews. Tungke means elder in people who are obliged to defend customs and institutions.Keywords: Meaning of Penghulu's Clothing, Minangkabau Customs, Customary Pengulu.Doi: http://dx.doi.org/10.23960/pesagi.v8.i2.2020.04